2017
DOI: 10.2147/copd.s150827
|View full text |Cite
|
Sign up to set email alerts
|

Real-life feasibility and effectiveness of home-based pulmonary rehabilitation in chronic obstructive pulmonary disease requiring medical equipment

Abstract: BackgroundPulmonary rehabilitation (PR) is a key treatment of chronic obstructive pulmonary disease (COPD) but studies are still needed to identify the most pertinent criteria to personalize this intervention and improve its efficacy.ObjectiveThis real-life retrospective study compared the effects of home-based PR on exercise tolerance, anxiety, depression, and health-related quality of life (HRQoL) in COPD patients, according to their medical equipment.MethodsExercise tolerance, anxiety, depression, and HRQoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 37 publications
(52 reference statements)
2
45
1
Order By: Relevance
“…This included five studies examining the 6MWT, 7-11 39 studies examining STS tests, 35 studies examining step tests 19,24, and 17 studies examining the Timed Up and Go (TUG). 17,19,24,33,42,49,50,[83][84][85][86][87][88][89][90][91][92] Ten studies examined more than one test, including four that examined STS and TUG, 17,42,48,49 four that examined two kinds of STS test, 29,32,44,45 and two studies (in three reports) that examined STS, TUG and step tests. 18,23,50 The PRISMA diagram is in Figure 1 and study characteristics are in Supplementary Tables S2-S5.…”
Section: Resultsmentioning
confidence: 99%
“…This included five studies examining the 6MWT, 7-11 39 studies examining STS tests, 35 studies examining step tests 19,24, and 17 studies examining the Timed Up and Go (TUG). 17,19,24,33,42,49,50,[83][84][85][86][87][88][89][90][91][92] Ten studies examined more than one test, including four that examined STS and TUG, 17,42,48,49 four that examined two kinds of STS test, 29,32,44,45 and two studies (in three reports) that examined STS, TUG and step tests. 18,23,50 The PRISMA diagram is in Figure 1 and study characteristics are in Supplementary Tables S2-S5.…”
Section: Resultsmentioning
confidence: 99%
“…However, exacerbation frequency and mortality were not significantly different between groups. COQUART et al [107] found that home-based PR in patients with NIV is feasible. They compared PR in patients on nocturnal CPAP, nocturnal NIV, LTOT or no additional equipment.…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%
“…Adherence to treatment can be broadly defined as “the extent to which a person's behavior corresponds with the agreed recommendations from a health-care provider.”[ 6 ] COPD is a chronic disease that typically necessitates the regular use of pharmacotherapies. [ 7 8 ] Nonadherence rate in COPD has been estimated to be more than 50%. [ 9 ] Poor adherence in COPD is influenced by many factors related to the patients, the illness, the prescribed medications, the society, and the health system.…”
Section: Introductionmentioning
confidence: 99%